Magnesium Alleviates Adverse Effects of Lead on Growth, Photosynthesis, and Ultrastructural Alterations of Torreya grandis Seedlings - Shen, Jie; Song, Lili; Müller, Karin; Hu, Yuanyuan; Song, Yang; Yu, Weiwu; Wang, Hailong; Wu, Jiasheng (Frontiers in Plant Science, 2016)
Magnesium (Mg2+) has been shown to reduce the physiological and biochemical stress in plants caused by heavy metals. To date our understanding of how Mg2+ ameliorates the adverse effects of heavy metals in plants is scarce. The potential effect of Mg2+ on lead (Pb2+) toxicity in plants has not yet been studied. This study was designed to clarify the mechanism of Mg2+-induced alleviation of lead (Pb2+) toxicity. Torreya grandis (T. grandis) seedlings were grown in substrate contaminated with 0, 700 and 1400 mg Pb2+ per kg-1 and with or without the addition of 1040 mg kg-1 Mg2+. Growth parameters, concentrations of Pb2+ and Mg2+ in the plants’ shoots and roots, photosynthetic pigment, gas exchange parameters, the maximum quantum efficiency (Fv/Fm), root oxidative activity, ultrastructure of chloroplasts and root growth were determined to analyze the effect of different Pb2+ concentrations in the seedlings as well as the potential ameliorating effect of Mg2+ on the Pb2+ induced toxicity. The growth of T. grandis seedlings cultivated in soils treated with 1400 mg kg-1 Pb2+ was significantly reduced compared with that of plants cultivated in soils treated with 0 or 700 mg kg-1 Pb2+. The addition of 1040 mg kg-1 Mg2+ improved the growth of the Pb2+-stressed seedlings, which was accompanied by increased chlorophyll content, the net photosynthetic rate and Fv/Fm, and enhanced chloroplasts development. In addition, the application of Mg2+ induced plants to accumulate five times higher concentrations of Pb2+ in the roots and to absorb and translocate four times higher concentrations of Mg2+ to the shoots than those without Mg2+ application. Furthermore, Mg2+ addition increased root growth and oxidative activity, and protected the root ultrastructure. To the best of our knowledge, our study is the first report on the mechanism of Mg2+-induced alleviation of Pb2+ toxicity. The gener¬ated results may have important implications for understanding the physiological interactions between heavy metals and plants, and for successful management of T. grandis plantations grown on soils contaminated with Pb2+.